On the HALA effect in the NMR carbon shielding constants of the compounds containing heavy p‐elements. Issue 19 (7th July 2016) - Rusakov, Yu. Yu.; Rusakova, Irina L.; Krivdin, Leonid B.
Abstract: The heavy atom (HA) effect on the NMR isotropic carbon shielding constants is computationally investigated in the series of model ethanes, ethylenes, and acetylenes, Cβ H3 Cα H2 XH n, Cβ H2 Cα HXH n, Cβ HCα XH n ( n  = 0, 1, 2, or 3 depending on X), where X covers p‐elements in the 13–17 groups of the 3–6 periods in as many as 60 compounds. Compounds under study provide diverse bonding situations for the α‐ and β‐carbons, which are characterized by the consecutive increase of the s‐character of the Cβ Cα and Cα X bonds, being one of the factors influencing spin‐orbit part of the HA on light atom effect (SO‐HALA). The "chalcogen dependence, " "pnictogen dependence, " "tetrel dependence, " and "triel dependence" are established for the 16th, 15th, 14th, and 13th groups, respectively. A well‐known "normal halogen dependence" for the 13 C NMR chemical shifts, established much earlier for the compounds containing 17th group elements, also revealed itself in all three series under investigation. The dependence of the spin‐orbit effects size depending on the number of the lone electron pairs (LEPs) on HA X has also been investigated. The comparison of theoretical 13 C NMR chemical shifts with experiment is performed for three representative tellurides. The HALA effect in this series has been shown to be strongly dependent on the number of tellurium LEPs. Abstract : Accurate, first‐principles nonrelativistic modeling is a versatile tool for the prediction of 13 C NMR spectra. Shielding constants are highly sensitive to the presence of heavy atoms, due to the manifestation of the so‐called HALA effect. This effect is computationally investigated in a series of model compounds, Cβ H3 Cα H2 XH n, Cβ H2 Cα HXH n, Cβ HCα XH n ( n  = 0, 1, 2, or 3 depending on X), where X covers p‐elements of the 13–17 groups of the 3–6 periods of the Periodic Table.